Respirable Uranyl-Vanadate-Containing Particulate Matter Derived From a Legacy Uranium Mine Site Exhibits Potentiated Cardiopulmonary Toxicity. (5th April 2018) - Zychowski, Katherine E; Kodali, Vamsi; Harmon, Molly; Tyler, Christina R; Sanchez, Bethany; Ordonez Suarez, Yoselin; Herbert, Guy; Wheeler, Abigail; Avasarala, Sumant; Cerrato, José M; Kunda, Nitesh K; Muttil, Pavan; et al.
Abstract: Exposure to windblown particulate matter (PM) arising from legacy uranium (U) mine sites in the Navajo Nation may pose a human health hazard due to their potentially high metal content, including U and vanadium (V). To assess the toxic impact of PM derived from Claim 28 (a priority U mine) compared with background PM, and consider the putative role of metal species U and V. Two representative sediment samples from Navajo Nation sites (Background PM and Claim 28 PM) were obtained, characterized in terms of chemistry and morphology, and fractioned to the respirable (≤ 10 μm) fraction. Mice were dosed with either PM sample, uranyl acetate, or vanadyl sulfate via aspiration (100 µg), with assessments of pulmonary and vascular toxicity 24 h later. Particulate matter samples were also examined for in vitro effects on cytotoxicity, oxidative stress, phagocytosis, and inflammasome induction. Claim 28 PM10 was highly enriched with U and V and exhibited a unique nanoparticle ultrastructure compared with background PM10 . Claim 28 PM10 exhibited enhanced pulmonary and vascular toxicity relative to background PM10 . Both U and V exhibited complementary pulmonary inflammatory potential, with U driving a classical inflammatory cytokine profile (elevated interleukin [IL]-1β, tumor necrosis factor-α, and keratinocyte chemoattractant/human growth-regulated oncogene) while V preferentially induced a different cytokine pattern (elevated IL-5, IL-6, and IL-10). Claim 28 PM10 was more potent than background PM10 in terms of in vitro cytotoxicity, impairment of phagocytosis, and oxidative stress responses. Resuspended PM10 derived from U mine waste exhibit greater cardiopulmonary toxicity than background dusts. Rigorous exposure assessment is needed to gauge the regional health risks imparted by these unremediated sites.